(untitled) - Crumbley, D. Larry (Chicago, 2005)
"Forensic accounting" is a growing area of practice in which the knowledge, skills and abilities of advanced accounting are combined with investigative expertise and applied to legal problems. Forensic accountants are often asked to provide litigation support where they are called on to give expert testimony about financial data and accounting activities. In other more proactive engagements, they probe situations using special investigative accounting skills and techniques. Some even see forensic accounting as practiced by skilled accounting specialists becoming part and parcel of most financial audits--an extra quality control step in the auditing process that will help reduce financial statement fraud. CCH's Forensic and Investigative Accounting (2nd Edition) is a complete and readily teachable text on today's most timely accounting topics. Written by three top accounting and forensic teachers, this text covers all the important underpinnings, as well as the substance of forensic accounting. It covers both litigation support and investigative accounting, examining the practical aspects of these two areas, as well as many of the newer technological areas. For the 2nd Edition, three new chapters have been added: - a new capstone chapter provides a case analysis that helps illustrate what is involved in a substantive forensic engagement from start to finish. - a new chapter covers computer forensics, which covers the use and recovery of electronic data for solving technology-based crimes - a new chapter covers economic damages resulting from wrongful terminations, wrongful death and other issues relating to personal injury. Forensic and Investigative Accounting explains and demonstrates how an effective forensic accountant needs a solid understanding of accounting, investigative auditing techniques, criminology, and courtroom procedures, as well as excellent communications skills, both written and oral. In today's litigious and highly regulated climate, all accountants--external, internal, forensic consultants, and corporate accountants--must possess this knowledge base and develop these techniques. This intriguing text provides unparalleled guidance to help develop the mindset and the skillset to meet the evolving challenges facing accountants today.
Keywords: Forensic accounting,Evidence, Expert,Fraud investigation,Kế toán pháp y,Bằng chứng, chuyên gia,Điều tra gian lận; United States.,United States.,United States